(untitled) (Siddhajyoti Interdisciplinary Journal, 2025)
This study addresses the integration of living values into ethical education curricula, aiming to enhance students’ moral growth and readiness to tackle ethical challenges in the 21st century. Set in the context of community schools in Nijgadh Municipality, it explores the impact of Living Values Education by engaging diverse stakeholders, including teachers, school administrators, parents, and students, through fifteen Focus Group Discussions (FGDs). This qualitative research method captures participants’ insights and lived experiences, offering a comprehensive view of Living Values Education’s role in ethical education. The study operates within a social constructivist and pragmatic philosophical framework, recognizing the collaborative nature of moral learning and its practical implications. Findings reveal that LVE significantly strengthens students’ empathy, ethical reasoning, and boring behavior, although curriculum consistency and stakeholder engagement challenges persist. This research underscores the value of LVE as an essential component of ethical education and suggests a need for further investigation into its long-term impacts and broader implementation strategies to prepare students effectively for the complex moral landscapes of contemporary society.